New Approaches to the Management of Primary and Secondary CNS Tumors - Roy Morgan, Lee (IntechOpen, 2017)
Several new concepts are reviewed and discussed in this book and allude to the transport of drugs bound to red blood cells into the vascular blood-brain barrier and into cancer cells. Such a transport system is novel and of potential therapeutic potential. It is the goal of this book to provide information and data that will be useful for others to develop new approaches for the management of CNS malignancies.